2010
DOI: 10.1016/j.jbspin.2009.05.011
|View full text |Cite
|
Sign up to set email alerts
|

New insights in synovial angiogenesis

Abstract: Angiogenesis is the formation of new capillaries from pre-existing vessels. A number of soluble and cell-bound factors may stimulate neovascularization. The perpetuation of angiogenesis involving numerous soluble and cell surface-bound mediators has been associated with rheumatoid arthritis (RA). These angiogenic mediators, among others, include growth factors, primarily vascular endothelial growth factor (VEGF) and hypoxia-inducible factors (HIFs), as well as pro-inflammatory cytokines, various chemokines, ce… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
50
0
1

Year Published

2010
2010
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 79 publications
(51 citation statements)
references
References 61 publications
0
50
0
1
Order By: Relevance
“…Although the etiology of RA remains controversial, the hallmark of the disease is characterized by inflammation of the synovial lining of diarthrodial joints, massive synovial proliferation, and an influx of inflammatory cells, macrophages, and lymphocytes through leaky angiogenic blood vessels (2)(3)(4). This cellular influx and synovial proliferation lead to the release of inflammatory cytokines and matrix-degrading enzymes, all of which contribute to the destruction of connective tissue, cartilage, and subchondral bone of the affected joints.…”
Section: Introductionmentioning
confidence: 99%
“…Although the etiology of RA remains controversial, the hallmark of the disease is characterized by inflammation of the synovial lining of diarthrodial joints, massive synovial proliferation, and an influx of inflammatory cells, macrophages, and lymphocytes through leaky angiogenic blood vessels (2)(3)(4). This cellular influx and synovial proliferation lead to the release of inflammatory cytokines and matrix-degrading enzymes, all of which contribute to the destruction of connective tissue, cartilage, and subchondral bone of the affected joints.…”
Section: Introductionmentioning
confidence: 99%
“…In addition, Wang et al found that PGK1 participated in angiogenesis by functioning to reduce disulfide bonds in the serine protease, plasmin, which leads to the release of the tumor blood vessel inhibitor angiostatin [26]. Angiostatin is important for the management of synovial inflammation and angiogenesis [27].…”
Section: Discussionmentioning
confidence: 99%
“…Angiogenesis is finely tuned by balances between pro-angiogenic and anti-angiogenic mediators such as growth factors, cytokines, chemokines, cellular adhesion molecules and others (Szekanecz et al, 2010). Of these, VEGF and its receptors are key regulators of the angiogenic process also in inflammatory synovium of RA.…”
Section: Rheumatoid Arthritismentioning
confidence: 99%